EKSISTENSI KEDUDUKAN DAERAH KHUSUS IBUKOTA JAKARTA SETELAH UNDANG-UNDANG IBUKOTA NEGARA DI SAHKAN (Lex Jurnalica, 2022)
AbstractThe plan to move the capital of the Unitary State of the Republic of Indonesia from the Special Capital Region of Jakarta to the North Penajam Paser Regency and part of the Kutai Kartanegara Regency has implications for the transfer of the status of the Special Capital Region from the Jakarta area to a new area. The status of the Special Capital Region in accordance with the Law of the Republic of Indonesia Number 29 of 2007 concerning the Provincial Government of the Special Capital City Region of Jakarta as the Capital of the Unitary State of the Republic of Indonesia provides an exception in the status of the position of municipalities and regencies within its territory where the appointment of mayors and regents is appointed by the Governor on the basis of consideration. DPRD DKI Jakarta Province from civil servants who meet the requirements compared to other provinces within the framework of the Unitary State of the Republic of Indonesia. Another difference is that there is no Regional Representative Council at the Municipal and Regency levels. In accordance with the Law of the Republic of Indonesia number 29 of 2007 concerning the Provincial Government of the Special Capital Region of Jakarta as the Capital of the Unitary State of the Republic of Indonesia, to assist the mayor/regent at the Mayor and Regency level, the City Council/Regency Council representing the community per sub-district, which of course Its function is different from that of the Municipal or Regency Regional Representative Council. Therefore, differences in matters relating to the position of mayor/regent and the functions of the Municipal/Regency Councils need to be studied further for the sake of conformity with the Law of the Republic of Indonesia number 23 of 2014 concerning Regional Government if the status of the State Capital held by Jakarta moves to North Penajam Passer Regency and Kutai Kartanegara Regency, East Kalimantan Province Keywords: Existence, DKI, IKN AbstrakRencana perpindahan Ibukota Negara Kesatuan Republik Indonesia dari Daerah Khusus Ibukota Jakarta ke wilayah Kabupaten Penajam Paser Utara dan sebagian wilayah Kabupaten Kutai Kartanegara memberi implikasi akan berpindahnya juga status Daerah Khusus Ibukota dari wilayah Jakarta ke wilayah baru. Status Daerah Khusus Ibukota sesuai  Undang-Undang Republik  Indonesia Nomor 29 TAHUN 2007 Tentang Pemerintahan Provinsi Daerah Khusus Ibukota Jakarta sebagai Ibukota Negara Kesatuan Republik Indonesia memberikan pengecualian  dalam status kedudukan kotamadya serta kabupaten di dalam wilayah nya yang penunjukan pejabar walikota dan bupati diangkat oleh Gubernur atas pertimbangan DPRD Provinsi DKI Jakarta dari pegawai negeri sipil yang memenuhi persyaratan dibanding provinsi lain di dalam kerangka Negara Kesatuan Republik Indonesia. Perbedaan lain yaitu tidak terdapatnya Dewan Perwakilan Daerah di tingkat Kotamadya dan Kabupaten. Sesuai Undang-Undang Republik Indonesia nomor 29 tahun 2007 tentang Pemerintahan Provinsi Daerah Khusus Ibukota Jakarta sebagai Ibukota Negara Kesatuan Republik Indonesia ,  untuk membantu walikota / bupati   di tingkat Walikota dan Kabupaten, dijabat oleh Dewan Kota/ Dewan Kabupaten yang mewakili masyarakat per kecamatan , yang tentu fungsi nya berbeda dengan Dewan Perwakilan Daerah Kotamadya atau Kabupaten. Oleh karena itu, perbedaan hal-hal yang berkaitan dengan jabatan walikota/bupati dan fungsi Dewan Kotamadya/Kabupaten perlu ditelaah lebih lanjut demi kesesuaian dengan Undang-Undang Republik Indonesia nomor  23 tahun 2014 tentang Pemerintahan Daerah apabila status Ibukota Negara yang disandang oleh Jakarta berpindah ke wilayah Kabupaten Penajam Passer Utara dan Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur Kata Kunci: Eksistensi, DKI, IKN